TNF inhibitors have a protective role in the risk of dementia in patients with ankylosing spondylitis: Results from a nationwide study. (August 2022) - Watad, Abdulla; McGonagle, Dennis; Anis, Saar; Carmeli, Reut; Cohen, Arnon D.; Tsur, Avishai M.; Ben-Shabat, Niv; Luigi Bragazzi, Nicola; Lidar, Merav; Amital, Howard
Abstract: Objectives: Ankylosing spondylitis (AS) is a chronic progressive and debilitating form of arthritis with associated extra-articular features including uveitis, intestinal and lung apical inflammation and psoriasis. Putative associations between AS and neurologic disorders has been relatively overlooked. The purpose of this study is to assess the link between AS and major neurologic disorders and whether treatment with Tumor-Necrosis-Factor inhibitors (TNFi) has an impact on that association. Methods: A retrospective cross-sectional study was carried out based on the Clalit Health Services (CHS) computerized database. AS patients were compared to age- and gender-matched controls with respect to the proportion of Alzheimer's disease (AD), Parkinson's disease (PD), epilepsy, and multiple sclerosis (MS). The impact of AS therapy (biologic vs conventional therapy) was assessed as well. Results: 4082 AS patients and 20, 397 age- and gender-matched controls were identified. AS was associated with a higher prevalence of AD (odds-ratio(OR) 1.46 [95%Confidence-interval(CI) 1.13–1.87], p = 0.003), epilepsy (OR 2.33 [95%CI 1.75–3.09] p < 0.0001) and PD (OR 2.75 [95%CI 2.04–3.72], p < 0.0001), whereas no statistically significant association was found for MS. Association with PD remained significant in the multivariate analysis (OR 1.49 [95%CI 1.05–2.13], p = 0.027). Within AS patients, the use of TNFi (OR 0.10 [95%CI 0.01–0.74], p = 0.024) were associated with a lowered risk of developing AD. Conclusion: AS is positively associated with AD, PD, and epilepsy but not MS. AS patients treated with TNFi have lower rates of AD. Graphical Abstract: ga1